The Problems and Alternative Solutions for the Implementation of Entrepreneurship Education in the Higher Education: A Literature Review - Adnan, Gunawan; Lailatussaadah, Lailatussaadah; Bin Jamil, Asyraf Isyraqy; Jannah, Misbahul; Muslim, Buhori; Erfiati, Erfiati (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to find some problems in implementing entrepreneurship education at higher education (university). The method used in this study was the literature review by searching articles on electronics journal database. The databases used in this study were Jstor, Sage, Proquest, Elsevier, Emerald, Insight, Springer Plus, and Google Scholars from 2003 to October 2019. Fifteen articles were found using five keywords: entrepreneurship education, entrepreneurial, unemployment, job seeker, and job creator. The data were analyzed by collecting the related articles, reducing them based on the topic discussion, displaying the data, and concluding. It was found that there were some problems faced during the implementation of entrepreneurship education. Thus, it can be concluded that the bigger the problem in the implementation of entrepreneurship education, the more extensive necessitate for the alternative formula. It is urged that further studies be conducted to expose more detailed comparisons between the problems found within the country and abroad. This action is considered as the foundation of a better service.